(untitled) (London Journal of Research In Humanities and Social Sciences, 2024)
Almost 85% of the territory of South-western Bulgaria is occupied by mountains, including the Rila and the Pirin massifs – the highest mountains on the Balkan Peninsula, reaching almost 3000 m above sea level. It is logical to assume that the Struma River Valley, which is the largest in this region, was a natural conduit for the spread of the Neolithic lifestyle from the Eastern Mediterranean towards Central Europe. But was this the actual situation? Only five settlements which have been dated to the various stages of the Early Neolithic Period have so far been registered in the Middle Struma Valley. The archaeological material from these sites reveals connections with the territories located to the south-west (northern Greece), to the west (Vardar River Valley) and to the east (Mesta River Valley). This indicates that the situation is much more complex, and the theory about the linear spreading of the agriculture from the south to the north along the Struma River Valley can no longer be regarded as proven. During the entire Early Neolithic period all natural mountain passes connecting the valleys of the Struma River, the Bregalnitsa River, and subsequently of the Vardar River to the west and Mesta River to the east, were actively used as communication routes. Thus, it rather is the West-east and east-west axis that played major role for the connectivity of the region of the Struma River Valley during the Early Neolithic period.